Assessing nonabrasive use of charcoal and its adsorptive microbial properties as a dentifrice - Pranav Chhaliyil; Bernd Schoel; Pradheep Chhalliyil (Wolters Kluwer Medknow Publications, 2021)
Background: Root caries and teeth sensitivity are the two most common clinical conditions resulting from poor oral hygiene and incorrect use of dental cleaning aids and methodology. Aim: This study is to evaluate the safe nonabrasive use of charcoal as dentifrice along with its adsorptive properties on salivary bacteria, yeast, and polysaccharides in biofilm matrix. Materials and Methods: The Mohs Scale of Mineral Hardness was used to evaluate abrasiveness of charcoal by investigating the scratches it produces on rubbing steel, copper, and nickel plates. The adsorptive ability of charcoal to bind bacteria was measured using the quantitative polymerase chain reaction. Efficiency to bind polysaccharides by charcoal was performed by the spectrophotometric analysis. Results: The Mohs hardness test showed that charcoal caused less scratches on nickel plates. As nickel plates have a lower hardness index than enamel, this indicates that charcoal might not be significantly abrasive to enamel. Some toothpaste caused scratches on the nickel plates. The benefits of adsorptive nature of charcoal in normal oral hygiene procedure exceed possible side effects by far. Activated charcoal can be used as a safe dentifrice if used in nanometer sized powder form causing minimum abrasion and it can still disturb biofilm formation by adsorbing microbes, biomolecules, acids, and therefore, offer protection to enamel and helps in the prevention of caries. Conclusion: Using finely powdered charcoal with "Gum and teeth rubbing with Index Finger, followed by Tongue cleaning" (GIFT) method is nonabrasive and so safe like other commercial toothbrushes and toothpastes. Further studies investigating the safe use of charcoal are recommended.